A right of Christian faithful to the just process - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2012)
In accord with the can. 221 § 1 of Code of Canon Law the Christian faithful can legitimately vindicate and defend the rights which they enjoy in the Church before a competent ecclesiastical court in accord with the norm of law. In this article the author is trying to explane the main norms in this topic and to present the role of judge, defender of the bond and advocate in the research of truth of every marriage.